Rethinking Indonesian Legislation on Wildlife Protection: A Comparison between Indonesia and the United States - Febrian Febrian; Lusi Apriyani; Vera Novianti (Sriwijaya Law Review, 2021)
In Indonesia, a crime against wildlife is still not well controlled. Several reasons are the fact that certain wildlife is still considered a threat by the community and the lack of implemented criminal sanctions. This paper compares the application of sanctions to perpetrators of wildlife crimes between Indonesia and America. Based on the Indonesian Law, Article 40(2) of the Law on Conservation of Living Natural Resources and their Ecosystems, a person who commits a crime against individual wild animals can be imprisoned for a maximum of five years and a maximum fine of one hundred million rupiahs. Meanwhile, the United States Law, the Endangered Species Act (ESA), charges wildlife criminals with criminal and civil penalties. In § 1540(a)(1) it provides that anyone who takes, imports, exports, transports or sells endangered species can be fined not more than $ 25,000. If the species is threatened in the group, the offender can be subject to a sentence of not more than $ 12,000. Also, additional criminal sanctions were imposed to revoke federal licenses, lease permits and hunting permits. This study aims to analyse criminal sanctions' enforcement in criminal cases against protected animals in courts in Indonesia and the United States to find best practices using normative legal research methods. The results show that the criminal sanctions against wildlife crimes in Indonesia have never reached the maximum sentence so that it is not sufficient to provide a deterrent effect for the perpetrators. Unlike in America, the imprisonment sanction for criminal sanctions for protected animals is still relatively weak, but fines and civil sanctions can be maximally applied.